A Viable Route for Lithium Ion Detection. Issue 3 (16th December 2013) - Gulino, Antonino; Lupo, Fabio; Cristaldi, Domenico A.; Pappalardo, Sebastiano; Capici, Calogero; Gattuso, Giuseppe; Notti, Anna; Parisi, Melchiorre F.
Abstract: Quartz substrates were first functionalized with 4‐ClCH2 C6 H4 SiCl3 and then allowed to react with 5‐(4′‐pyridylazo)‐25, 26, 27‐tris(ethoxycarbonylmethoxy)‐28‐hydroxycalix[4]arene in a covalent fashion to yield a hybrid material with an immobilized monolayer of a chromogenic sensing agent. The structural characterization of this ionophore monolayer on silica surfaces was performed by X‐ray photoelectron spectroscopy. This technique was also used together with UV/Vis spectroscopy to investigate the ionophoric properties of the monolayer, which was found to reversibly recognize and bind lithium ions at ppm levels even in the presence (in a comparable concentration) of highly competitive cations such as Na + . Overall, our procedure shows that a single‐molecule property can be successfully transferred to a solid‐state device. Abstract : A monolayer of 5‐(4′‐pyridylazo)‐25, 26, 27‐tris(ethoxycarbonylmethoxy)‐28‐hydroxycalix[4]arene molecules covalently grafted on quartz substrates provides recognition properties for Li ions at ppm levels in aqueous solutions. The system is fast, reversible, and selective.